Green Concrete from Sustainable Recycled Coarse Aggregates: Mechanical and Durability Properties. (2nd February 2015) - Jain, Neeraj; Garg, Mridul; Minocha, A. K.
Abstract : Present investigations deal with the development of green concrete (M 30 grade) using recycled coarse aggregates for sustainable development. Characterization of recycled coarse aggregates showed that physical and mechanical properties are of inferior quality and improvement in properties was observed after washing due to removal of old weak mortar adhered on its surface. The influence of natural coarse aggregates replacement (50 and 100%) with recycled coarse aggregate on various mechanical and durability properties of hardened concrete were discussed and compared with controls at different w/c ratio. Improvements in all the engineering properties of hardened concrete were observed using washed recycled coarse aggregates. The compressive strength of 28-day hardened concrete containing 100% washed recycled aggregate was slightly lower (7%) than concrete prepared with natural aggregates. Water absorption, carbonation, and rapid chloride penetration test were conducted to assess the durability of the concrete. Concrete was found moderately permeable for chloride ions penetration and no carbonation was observed in all the concrete mixes studied.